What Should a Good Concept of Labour Do? The Case of Digital Labour - Miguel Rudolf-Cibien; Marc-Antoine Pencolé (Italian Labour Law e-Journal)
The term ‘digital labour’ has gained significant traction in academic discussions, yet its meaning remains unclear and widely contested. This paper argues that to advance the debate on the nature of digital labour, we must shift the discussion to the meta-semantic level and examine the functions of the concept of labour. It is not enough to simply ask “What is labour?” – we must also ask “What should a good concept of labour do?”. We will clarify this shift in conceptual analysis from an epistemological perspective, drawing on the field of conceptual engineering, particularly the work of social critical theorist Sally Haslanger, who has extensively explored the re-engineering of social and political concepts. We will then argue that the predominant focus on a macro-structurally oriented concept of digital labour is rarely questioned, despite the existence of alternative approaches. Finally, we will outline the key features that a good concept of digital labour should possess in today’s context, namely an intersubjectively-oriented concept grounded in recognition structures specific to the sphere of work.